2014
DOI: 10.1002/jrs.4542
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of optimized SERS active gel substrates for painting and paper substrates by unilateral NMR profilometry

Abstract: In order to realize a surface enhanced Raman spectroscopy (SERS) gel protocol with portable Raman instrumentation, this contribution oversees the optimization of a removable SERS active methylcellulose gel and the applicability of an innovative gelatin substrate. Analytical evaluations by non‐invasive portable nuclear magnetic resonance (NMR) profilometry with regards to methylcellulose and gelatin film penetration and removal from an unvarnished painted surface and commercial dyed paper substrates have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Moreover, degradation processes or bad state of conservation of the art object may further affect the analyses of the blue dye. In the last decade, the successful application of the high sensitive surface enhanced (resonance) Raman spectroscopy [SE(R)RS] for the detection of organic dyes in works of art has strongly improved the possibility of identifying fluorescent organic dyes according to minimal invasive [10][11][12][13][14] and microdestructive approaches [15][16][17]. Up to the present, the majority of the developed SERS procedures dealt mainly with the detection of red and yellow dyes [15][16][17][18][19][20][21][22][23][24][25][26], whereas only a few works have investigated the characterization of indigoids by means of SERS/SERRS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, degradation processes or bad state of conservation of the art object may further affect the analyses of the blue dye. In the last decade, the successful application of the high sensitive surface enhanced (resonance) Raman spectroscopy [SE(R)RS] for the detection of organic dyes in works of art has strongly improved the possibility of identifying fluorescent organic dyes according to minimal invasive [10][11][12][13][14] and microdestructive approaches [15][16][17]. Up to the present, the majority of the developed SERS procedures dealt mainly with the detection of red and yellow dyes [15][16][17][18][19][20][21][22][23][24][25][26], whereas only a few works have investigated the characterization of indigoids by means of SERS/SERRS.…”
Section: Introductionmentioning
confidence: 99%
“…While leaving the treated surface free of silver residues, SEM analysis revealed that material detachments of up to 50 microns in diameter may be caused by the peeling process. An upgraded formulation in which both the viscosity and nanoparticle preparation were optimized compared to the initial recipe has been shown to significantly reduce substrate losses . Leona et al .…”
Section: Sers In Art and Archaeology: Standard Procedures And Latest mentioning
confidence: 99%
“…To this end, a small but growing number of papers have been published demonstrating the use of flexible substrates based on acrylic gels [182,183], methylcellulose pastes [119], gelatin [120], or agar-agar gel [187,241], optionally loaded with a mild micro-extractant, often based on ethylenediaminetetraacetic acid (EDTA) [240]. The analytical procedure either involves mixing the gel with nanoparticles, or using the gels to extract a minute and nearly invisible amount of dye for later analysis with SERS after deposition of colloidal silver particles on the face that was previously in contact with the artifact.…”
Section: Surface-enhanced Raman Spectroscopy (Sers)mentioning
confidence: 99%